The Creator and His Attributes in the Maturidi Doctrine (Journal of Philosophy Culture and Political Science, 2018)
The fact that God is also he one – is the main postulate of Islamic theology. In the Koran and the Hadith special attention is paid to this subject and it is considered correct to call God by the special names as He is a creator of live and lifeless matter and the master of all worlds. One of the most famous Sunni theologians Imam Abu-Mansour in the theological work of «Kitabu-t-taukhid», based on the Koran and the hadisakh, has shared valuable thoughts concerning names of Allah and has tried to open a concept of God.To prove the validity of the views, the thinker has drawn important conclusions and the conclusions concerning religious sources, and also has paid special attention to works of old and modern theological schools, thinkers ideas and views at the same time he has tried to define their wrong directions. In the doctrine about God and monotheism, Al-Maturidi cites as an example known in Islamic philosophy and theology of the proof: Hudus, Nizam, Taman, Tauarud, etc. At the same time, according to the doctrine of his mentor Abu Hanifa, he also has tried to describe an image of God. According to Al-Maturidi’s doctrine, the image of the Creator is absolute and isn’t similar to the phenomena created by Him at all. Views of the Imam Maturidi about God, the world, people and their relationship, a prophecy and othertheological subjects became beginning for maturidizm creation.Key words: al-Maturidi, Аllah, syfat, kalam, takwin, ‘azali, qadim, mu’tazila, jahmia, jawhar, araz, mushabbiha.